Presbyopic LASIK using the Supracor algorithm and micromonovision in presbyopic myopic patients: 12-month visual and refractive outcomes. Issue 2 (February 2023) - Adam, Thomas; Boucenna, William; Lussato, Mikhael; Hagege, Alain; Berguiga, Marouen; Marechal, Marie; Froussart-Maille, Françoise; Delbarre, Maxime
Abstract : This retrospective bicentric study including 50 eyes (25 patients) evaluated the visual and refractive outcomes for bilateral myopic SUPRACOR and micromonovision using the Teneo 317 M2 platform. Abstract : Purpose: To evaluate the visual and refractive outcomes for presbyopia and myopia treatment using the Teneo 317 M2 platform and the myopic Supracor algorithm. Setting: Percy Military Hospital and Private Laser Victor Hugo Center, Paris, France. Design: Observational retrospective nonrandomized study. Methods: 50 eyes (25 patients) treated with bilateral myopic Supracor and micromonovision using the Teneo 317 M2 platform and followed up for 12 months. Study outcomes included binocular and monocular visual acuities (without correction for distance and near vision), the spherical equivalent, predictability, stability, safety, optical aberrations, and complications. Results: The mean age was 50.6 ± 2.7 years, and the mean preoperative spherical equivalent was −2.6 ± 1.4 diopters. At 12 months postoperatively, the mean binocular uncorrected distance visual acuity was 0.02 ± 0.03 logMAR, and 24 patients (96%) achieved an acuity of 20/25 or better. The binocular uncorrected near visual acuity was equal to Jaeger 1 in 18 patients (72%) and Jaeger 2 or better in 23 patients (92%). 12 eyes (24%) had lost 1 Snellen line, and 1 eye (2%) had lost 2 Snellen lines of monocular corrected distance visual acuity. No cases required retreatment; however, 1 eye (2%) underwent revision surgery because of diffuse lamellar keratitis. Conclusions: This study suggests that Supracor using the Teneo 317 M2 platform is a safe and effective technique for myopia and presbyopia treatment. Supracor is therefore a viable alternative to monovision for presbyopia and myopia. However, a careful patient selection is essential to satisfy realistic expectations.